The correlation between histopathology of herniated lumbar intervertebral disc and clinical findings - Ammar, Ahmed; Alwadei, Ali; Al Hayek, Ali; Alabbas, Faisal; Almatrafi, Faisal; Elshawarby, Mohammed (Asian Journal of Neurosurgery, 2020)
Objective: Prolapsed lumbar disc is one of the most frequent diseases, which is usually presented by motor and sensory deficits. Consistency of herniated disc may play a significant role in surgical treatment and postoperative improvement. The objective of this study is to assess whether the histopathological degeneration in the sample of lumbar discs operated on is correlated to clinical variables and surgical outcomes. Materials and Methods: A randomized double-blind prospective study of lumbar disc prolapse cases over a period of 24 months was done. Forty cases were initially included in the study. All the included cases with a scheduled lumbar discectomy in the Department of Neurosurgery, King Fahd University Hospital, Al-Khobar, Saudi Arabia, during this period were examined histologically. Results: Finally, 21 patients were only considered in this study due to loss of follow-up of the other 19 patients; of these 21 patients, 18 were male and 3 were female. The youngest patient was 32 years old, and the oldest was 72 years old. There is no significant correlation between the major histopathological changes of the prolapsed discs and the clinical findings of low back pain (correlation coefficient = 0.058, P < 0.8), duration of sciatica (correlation coefficient = −0.337, P < 0.1), paresthesia (correlation coefficient = 0.111, P < 0.6), motor weakness (correlation coefficient = 0.274, P < 0.2), and reflex (correlation coefficient = 0.081, P < 0.7). Meanwhile, the correlation coefficient between numbness and histopathological degeneration score (HPDS) is not defined because all reported cases were presented with numbness. Conclusions: There is no significant correlation between the histopathological changes of the prolapsed discs and some clinical findings. Moreover, the different types of prolapsed discs' histopathological changes have no impact on the outcome of the surgery. We also concluded that the disc material undergoes certain degenerative processes with age.
Keywords: Herniated lumbar disc; histopathology; low back pain; microdiscectomy; sciatica